Hair cell toxicology: With the help of a little fish - Barrallo-Gimeno, Alejandro; Llorens, Jordi (Frontiers in Cell and Developmental Biology, 2022)
Hearing or balance loss are disabling conditions that have a serious impact in those suffering them, especially when they appear in children. Their ultimate cause is frequently the loss of function of mechanosensory hair cells in the inner ear. Hair cells can be damaged by environmental insults, like noise or chemical agents, known as ototoxins. Two of the most common ototoxins are life-saving medications: cisplatin against solid tumors, and aminoglycoside antibiotics to treat infections. However, due to their localization inside the temporal bone, hair cells are difficult to study in mammals. As an alternative animal model, zebrafish larvae have hair cells similar to those in mammals, some of which are located in a fish specific organ on the surface of the skin, the lateral line. This makes them easy to observe in vivo and readily accessible for ototoxins or otoprotective substances. These features have made possible advances in the study of the mechanisms mediating ototoxicity or identifying new potential ototoxins. Most importantly, the small size of the zebrafish larvae has allowed screening thousands of molecules searching for otoprotective agents in a scale that would be highly impractical in rodent models. The positive hits found can then start the long road to reach clinical settings to prevent hearing or balance loss.